2021
DOI: 10.7717/peerj.10751
|View full text |Cite
|
Sign up to set email alerts
|

Age-related abnormalities of thalamic shape and dynamic functional connectivity after three hours of sleep restriction

Abstract: Background Previous neuroimaging studies have detected abnormal activation and intrinsic functional connectivity of the thalamus after total sleep deprivation. However, very few studies have investigated age-related changes in the dynamic functional connectivity of the thalamus and the abnormalities in the thalamic shape following partial sleep deprivation. Methods Fifty-five participants consisting of 23 old adults (mean age: 68.8 years) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…A stronger magnetic field e.g., 3T or 7T would increase signal to noise of the images and therefore increase the accuracy of subcortical segmentations. Moreover, in the current study, mean age of patients were higher than healthy subjects and it has been demonstrated that age has an important effect in gray matter structures in subjects with sleep disturbances (61,62). Smaller total brain size could be argued to contribute in the group difference reported in this work.…”
Section: Limitationssupporting
confidence: 43%
“…A stronger magnetic field e.g., 3T or 7T would increase signal to noise of the images and therefore increase the accuracy of subcortical segmentations. Moreover, in the current study, mean age of patients were higher than healthy subjects and it has been demonstrated that age has an important effect in gray matter structures in subjects with sleep disturbances (61,62). Smaller total brain size could be argued to contribute in the group difference reported in this work.…”
Section: Limitationssupporting
confidence: 43%
“…Previous studies have shown that altered SPG function is complexly correlated with sleep quality and cognitive changes, including mood, memory, and attention ( 46 50 ). After sleep restriction, the functional connectivity variability of the SPG and thalamus was reduced and was significantly correlated with insomnia severity ( 51 ). This finding is consistent with the significant negative correlation between the reduced FCS values in the left SPG and sleep efficiency in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al and Xu et al (C. Li et al, 2020 ; Xu et al, 2018 ) have shown altered dwell time and transit between FC states after SD. Long et al (Long et al, 2021 ) have examined the age‐related changes in FC variability of the thalamus after partial SD, and reported reduced FC variability between the left thalamus and the left superior parietal cortex in young adults after 3 h of sleep restriction. However, the FC states analysis measured the patterns of whole brain dynamic FC (Allen et al, 2014 ; Bolton et al, 2020 ), rather than the dynamic FC architecture of a specific region.…”
Section: Introductionmentioning
confidence: 99%